2020
DOI: 10.1007/s00787-020-01634-0
|View full text |Cite
|
Sign up to set email alerts
|

Discharge interventions from inpatient child and adolescent mental health care: a scoping review

Abstract: The post-discharge period is an extremely vulnerable period for patients, particularly for those discharged from inpatient children and adolescent mental health services (CAMHS). Poor discharge practices and discontinuity of care can put children and youth at heightened risk for readmission, among other adverse outcomes. However, there is limited understanding of the structure and effectiveness of interventions to facilitate discharges from CAMHS. As such, a scoping review was conducted to identify the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Innovations for integrated care show promising evidence for reducing the rate of emergency admissions to an acute ward, the LOS in both the emergency department and inpatient setting, and the rehospitalisation rate after discharge. Thus, integrated care not only improves health outcomes [ 17 , 18 ] and effectively reduces psychiatric hospitalisation [ 19 ]—this review adds that signposting to psychological interventions also reduces emergency readmissions in paediatric emergency settings too. Whilst there is sometimes no alternative to hospitalisation for medical emergencies [ 16 , 17 ], integrating psychiatric care into emergency services helps to triage effectively, intervene earlier, and signpost to therapeutic support, reducing lengthy and repeat hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovations for integrated care show promising evidence for reducing the rate of emergency admissions to an acute ward, the LOS in both the emergency department and inpatient setting, and the rehospitalisation rate after discharge. Thus, integrated care not only improves health outcomes [ 17 , 18 ] and effectively reduces psychiatric hospitalisation [ 19 ]—this review adds that signposting to psychological interventions also reduces emergency readmissions in paediatric emergency settings too. Whilst there is sometimes no alternative to hospitalisation for medical emergencies [ 16 , 17 ], integrating psychiatric care into emergency services helps to triage effectively, intervene earlier, and signpost to therapeutic support, reducing lengthy and repeat hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need to monitor admissions, readmissions, and length of hospital stay (LOS), as proxies for efficient and sustained recovery, with minimal institutionalisation. Recent evidence indicates that integrating multidisciplinary staffing to provide both medical and psychiatric triage, as well as delivering low-intensity psychological therapy within acute psychiatric settings improved service efficiency and treatment capacity [ 19 ]. Yet, there is limited evidence whether these therapies improve healthcare efficiency when integrated into paediatric emergency settings.…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient and tailored post-discharge support services for patients and their attachment figures could support a successful readjustment and accompany the challenging transition period after discharge [13,29]. Ideally, case-leading therapists of inpatient treatment seamlessly accompany the reintegration phase for some more weeks after discharge and support readjustment to daily (school) life as well as transfer of treatment successes.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the context of aftercare, E-Mental-Health services can complement inpatient treatment and close the gap to outpatient treatment by relying on existing therapeutic relationships to seamlessly support the transition from psychiatric hospital to daily life in a lowthreshold manner [34,37]. A recent review on discharge interventions from inpatient child and adolescent mental health care identified only two randomized controlled trials in this area, none of which examined a digitally supported intervention [29]. However, one feasibility study discussed in the review [29] showed a general interest in downloading a smartphone-based application for a digital safety plan at the time of discharge [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation